Новый вид жгутиконосцев — Parastasia granulosa sp. n. (Protozoa, Euglenoididae) из кишечника циклопов - Палиенко, Л.П. (Вестник зоологии, 1980)
Morphology and life cycle of the parasitic euglenoidid species Parastasia granulosa sp. n. (new for science) from guts of Macrocyclops albidus collected in the bogged up lake near Kulikov settlement in the Kiev environs are described and illustrated. The new species differs from all the known ones of the genus in that flagellate individuals after each division (except for the last one) do not drift apart and form a morula-like colony. The separated individuals move only by means of a flagellum without metabolic changes in the body shape